The effects of interpreting training on executive functions: A longitudinal study - Ghiselli, Serena; Russo, Mariachiara; Tomasetto, Carlo (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
Previous research has yielded conflicting evidence as regards the benefits of interpreting training on the development of cognitive processes involved in simultaneous interpreting. In this longitudinal study, we examined the changes in memory and inhibition profiles of two cohorts of interpreting students (study group) and two cohorts of translation students (control group) across three (cohort 1) or two measurement sessions (cohort 2) over their Master’s courses. Results from linear mixed effects models (LME) showed that performance improved for both groups on all measures except for inhibition, but no significant differences between groups in the rate of change were observed. Interpreting students displayed an advantage in inhibition and associative memory already at baseline. Overall, findings suggest that the changes in memory and inhibition profiles of interpreting students may not be related to academic training in interpreting and students with advantages in inhibition and associative memory may self-select for interpreting training.